Fast modelling of tidal phenomenon for the Straits of Malacca using laplace spatial interpolation technique [electronic resource] - Malavige Don Eranda Kanchana Gunathilaka, 1978-, author 653572; Mohd. Razali Mahmud, 1961-, supervisor 544288; Fakulti Geoinformasi dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Ph.D (Hydrograpgy))